Dealing with Moments of Crisis Interculturally in Educational Virtual Exchanges: A Sino-Finnish Case Study - Jun Peng; Fred Dervin (MDPI AG, 2022)
Being able to deal with "moments of crisis" is crucial in intercultural communication. Using identities as an analytical lens, this paper examines different types of "moments of crisis" identified in educational virtual exchanges between Chinese and Finnish university students. The study shows that the participants use soothing and code-switching as strategies in these moments of crisis to "do" interculturality, i.e., to achieve interactional arrangements (e.g., moving the discussion forward) and self-other alignments (e.g., saving face). Focusing on soothing as a positive strategy and code-switching as an avoidance strategy in dealing with "moments of crisis", we also scrutinize the emergence of the identities of mediator, fence-sitter, and facilitator in the students' behaviors. Finally, students' working experience, language use, and physical surroundings are identified as having a potential influence on their use of soothing and code-switching during the online intercultural interactions. Recommendations for preparing students for international virtual exchanges conclude the paper.